USERS VISION OF A FAMILY HEALTH UNIT ABOUT NATIONAL HEALTH SYSTEM (Fiep Bulletin - online, 2015)
The Brazilian National Health System  (SUS - Brazilian acronym of SistemaÚnico de Saúde) was created in 1988 by the Constitution and regulated by law No. 8080/90 and No. 8,142 / 90 , the organic laws of health , in order to change the situation of inequality in health care making mandatory the public service to any citizen . Through SUS, all citizens are guided to consultations, tests, hospitalizations and treatments in hospitals linked to local, state or federal level, whether public or private, contracted by the public health manager. Based on these assumptions, this study has the overall objective to know the vision of users of a Family Health Unit of the SUS, including the comprehension of the users about the principles and guidelines of the SUS; identifying users' knowledge about the respect for their rights; and their participation in decision-making processes at the local level. An exploratory, descriptive and empirical research with a qualitative approach was performed using as a method of script a semi-structured questionnaire with objective and subjective questions, and the data were analyzed using the technique of discourse analysis of the collective subject of Lefevre. Given this reality, it was possible making strengthen studies about SUS in the perspective of users, aiming to clarify the lived experiences and perceptions of those who are served by the system, contributing to the work of many professionals, managers and researchers who deal with SUS every day.
Keywords: Knowledge; Users; Family Health.